Modelling the demand for loans to the private sector in the euro area - Alessandro Calza; Christine Gartner; Jo\~ao Sousa (European Central Bank (ECB), 2001)
This paper studies the determinants of loans to the private sector in the euro area. Using the Johansen methodology, the study identifies one cointegrating relationship linking real loans, GDP and interest rates. This relationship implies that in the long-run real loans are positively related to real GDP and negatively to real short-term and long-term interest rates. Both the signs and the magnitude of the coefficients suggest that the cointegrating vector describes a long-run demand equation. The short-run dynamics of the demand for euro area real loans is subsequently modelled by means of a Vector Error Correction Model (VECM). A number of specification tests performed on the VECM produce satisfactory results, with tests of stability of the model parameters showing no signs of structural breaks during the sample period (1980 Q1 - 1999 Q2). All of this suggests that developments in real loans to the private sector in the euro area can be reasonably explained by the model
Keywords: C32; C51; 330